2009
DOI: 10.1002/cphc.200900328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fullerenes on Phospholipid Membranes: A Langmuir Monolayer Study

Abstract: We investigate two-component Langmuir monolayers of dipalmitoylphosphatidylcholine (DPPC)/C(60) by recording surface pressure/area (pi/A) and surface potential/area (DeltaV/A) isotherms and by direct Brewster angle microscopy (BAM) imaging. Atomic force microscopy (AFM) is employed to study morphologies of the mixed monolayers transferred to a solid substrate by the Langmuir-Blodgett technique. C(60) is shown to have little influence on isotherms of the DPPC/C(60) monolayers even at a molar fraction as high as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 44 publications
4
43
0
Order By: Relevance
“…Yang and Wang investigated two-component Langmuir monolayers of DPPC/fullerene by recording surface pressure/area and surface potential/area isotherms and by direct Brewster angle microscopy imaging. [66] It showed that the isotherms and elastic modulus versus π curves of the DPPC/fullerene were remarkably similar to the pure DPPC monolayers even at a molar fraction as high as Xc 60  =  0.3, suggesting little effect of fullerene. In our simulation, the ratio of the fullerene/DOPC is about 0.05, which is smaller than the experimental ratio.…”
Section: Resultsmentioning
confidence: 92%
“…Yang and Wang investigated two-component Langmuir monolayers of DPPC/fullerene by recording surface pressure/area and surface potential/area isotherms and by direct Brewster angle microscopy imaging. [66] It showed that the isotherms and elastic modulus versus π curves of the DPPC/fullerene were remarkably similar to the pure DPPC monolayers even at a molar fraction as high as Xc 60  =  0.3, suggesting little effect of fullerene. In our simulation, the ratio of the fullerene/DOPC is about 0.05, which is smaller than the experimental ratio.…”
Section: Resultsmentioning
confidence: 92%
“…C s −1 describes the relationship between the surface pressure increase and the area per molecule decrease. A higher value of C s −1 is indicative of a less compressible monolayer [44,45].…”
Section: Parameters Studied From the Surface Pressure-area Langmuir Imentioning
confidence: 98%
“…A higher value of C À1 s is indicative of a less compressible monolayer. [25,26] The A min value corresponds to the mean area occupied by one molecule of EPC in the surface layer just before collapse. It is indicative of both the molecular packing and the interactions between the monolayer components.…”
Section: Surface Pressure-molecular Area Isothermsmentioning
confidence: 99%